The effect of body mass index on tooth eruption and dental caries - Mohamed Salim Younus; Karam Ahmed; Duran Kala (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Children were compared to their siblings, cousins or peers regarding the eruption of their permanent teeth. Genetic and environmental factors can affect dental development and, therefore, the body mass index (BMI) could be considered as a factor that may influence dental development. Purpose: To determine any possible association between BMI and either dental caries or the eruption of permanent teeth (central incisor and molar). Methods: A cross-sectional study was completed for six-year-old school children. A total of 218 children (116 boys, 102 girls) from public elementary schools in Erbil City were entered into the study. Dental caries assessments were carried out using the WHO criteria for decayed, missing and filled primary teeth and indices (DMFT). BMI was used to classify obesity status. Results: Overall, 27.98% of the children were classified as overweight, 59.17% as normal and 12.84% as underweight. The DMFT was 5.247, while 12.39% of the children were caries-free. Conclusions: Children of normal weight had most permanent teeth erupted and a low caries index. Underweight children had fewer erupted teeth and a higher caries index. The complex relationship between body composition and oral health should be considered in paediatric patients.